Implementation of the Pancasila Student Profile Strengthening Project (P5) in Enhancing Student Character - Prasetiyo, Nova Tri; Sariyani, Sariyani; Haq, Muh Dliyaul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme "Voice of Democracy" at MAN 2 Trenggalek. A qualitative approach was employed through interviews and group discussions with students, a teacher of Akidah Akhlaq, and guidance counselor (BK). The research stages include planning, implementation, and evaluation of the project. The findings indicate an improvement in students' understanding of democratic values and the development of tolerant and responsible character traits. Students reported feeling more motivated to actively participate in discussions and activities, creating an inclusive learning environment. The discussion highlights the importance of integrating Pancasila values into character education and the challenges faced in teaching ethics of expression. This research provides recommendations to strengthen collaboration among schools, parents, and the community in supporting character education based on democratic values.